Mindfulness and negative emotions among Chinese college students: chain mediation effect of rumination and resilience - Shi, Keke; Feng, Guoyan; Huang, Qiyong; Ye, Meilin; Cui, Hongbo (Frontiers in Psychology, 2023)
Objective This study examines the mediation effect of rumination and resilience between the relationship of mindfulness and negative emotions in Chinese college students. Method A total of 3038 college students (19.94 ± 1.10) were investigated by Mindfulness Attention Awareness Scale (MASS), Rumination Response Style Scale (RRS), Resilience Scale (RES) and Depression-anxiety-pressure scale (DASS-21), and the mediation analyses were conducted by adopting PROCESS macro in the SPSS software. Results ① Mindfulness was negatively associated with rumination and negative emotions (r = -0.69, -0.72; P ＜ 0.01), and positively associated with resilience (r = 0.63, P ＜ 0.01). Rumination was negatively associated with resilience(r = -0.59, P ＜ 0.01), and positively associated with negative emotions (r = 0.83, P ＜ 0.01). Resilience was negatively associated with negative emotions (r = -0.71, P ＜ 0.01). ② Mindfulness can not only directly predict negative emotions (95%CI: -0.12~-0.09) but also affects negative emotions through three indirect paths: Rumination was a mediator (95%CI:-0.24~-0.20), resilience was a mediator (95%CI:-0.07~-0.06), and resilience and rumination were a chain mediator (95%CI:-0.04~-0.03). Conclusion Mindfulness not only influences negative emotions directly, but also through the mediating effect of rumination and resilience indirectly.